Clinical significance of worsening versus stable preradiographic MRI lesions in a cohort study of persons at higher risk for knee osteoarthritis. Issue 9 (14th October 2015) - Sharma, Leena; Nevitt, Michael; Hochberg, Marc; Guermazi, Ali; Roemer, Frank W; Crema, Michel; Eaton, Charles; Jackson, Rebecca; Kwoh, Kent; Cauley, Jane; Almagor, Orit; Chmiel, Joan S
Abstract : Background: Whether preradiographic lesions in knees at risk for osteoarthritis are incidental versus disease is unclear. We hypothesised, in persons without but at higher risk for knee osteoarthritis, that: 12–48 month MRI lesion status worsening is associated with 12–48 month incident radiographic osteoarthritis (objective component of clinical definition of knee osteoarthritis) and 48–84 month persistent symptoms. Methods: In 849 Osteoarthritis Initiative participants Kellgren/Lawrence (KL) 0 in both knees, we assessed cartilage damage, bone marrow lesions (BMLs), and menisci on 12 month (baseline) and 48 month MRIs. Multivariable logistic regression was used to evaluate associations between 12–48 month worsening versus stable status and outcome (12–48 month incident KL ≥1 and KL ≥2, and 48–84 month persistent symptoms defined as frequent symptoms or medication use most days of ≥1 month in past 12 month, at consecutive visits 48–84 months), adjusting for age, gender, body mass index (BMI), injury and surgery. Results: Mean age was 59.6 (8.8), BMI 26.7 (4.2) and 55.9% were women. 12–48 month status worsening of cartilage damage, meniscal tear, meniscal extrusion, and BMLs was associated with 12–48 month incident radiographic outcomes, and worsening of cartilage damage and BMLs with 48–84 month persistent symptoms. There was a dose-response association for magnitude of worsening of cartilage damage, meniscal tear, meniscal extrusion, and BMLs and radiographic outcomes, and cartilage damage and BMLs and persistent symptoms. Conclusions: In persons at higher risk, worsening MRI lesion status was associated with concurrent incident radiographic osteoarthritis and subsequent persistent symptoms. These findings suggest that such lesions represent early osteoarthritis, and add support for a paradigm shift towards investigation of intervention effectiveness at this stage.